2015
DOI: 10.22500/sodality.v2i1.9411
|View full text |Cite
|
Sign up to set email alerts
|

PERUBAHAN STRUKTUR AGRARIA DAN IMPLIKASINYA TERHADAP GERAKAN PETANI PEDESAAN (Analisis Karakter Forum Paguyuban Petani Jasinga Pasca PPAN)

Abstract: Masyarakat Curug dan Tegal Wangi memiliki masalah yang berkaitan dengan pendudukan lahan. Dua <br />aspek yang berubah setelah penurunan pendudukan lahan adalah penurunan kepemilikan lahan dan tingkat pendapatan. Munculnya Forum Paguyuban Petani Jasinga merupakan bagian dari strategi mereka untuk menanggulangi masalah di atas. Penelitian ini bertujuan untuk menganalisis pengaruh agraria terhadap perubahan struktur karakter organisasi. Hasil penelitian menunjukkan tidak ada pengaruh perubahan status sosia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Meanwhile, peasant organization was not only formed to do that, but also taking further steps in developing economic, educational, or cultural institutions in the society as the basis of the movement. Such stagnations on movement improvement was also experienced by the peasants of Kalibakar, South Malang; Sukamulya Village, Rumpin District, Bogor Regency; and also Curug Village and Tegal Wangi Village, Jasinga District (Rahmah & Soetarto, 2015;Lestari & Purwandari, 2015).…”
Section: Literature Reviewmentioning
confidence: 78%
See 2 more Smart Citations
“…Meanwhile, peasant organization was not only formed to do that, but also taking further steps in developing economic, educational, or cultural institutions in the society as the basis of the movement. Such stagnations on movement improvement was also experienced by the peasants of Kalibakar, South Malang; Sukamulya Village, Rumpin District, Bogor Regency; and also Curug Village and Tegal Wangi Village, Jasinga District (Rahmah & Soetarto, 2015;Lestari & Purwandari, 2015).…”
Section: Literature Reviewmentioning
confidence: 78%
“…Therefore, it can be concluded that Indonesian peasants -from the colonial era to the present day -have never had the ability to develop modern movement organization with professional management. The success of the reclaiming/ looting movement so far has been triggered by the unstable political situation, and supported by networking parties outside the peasants such as socio-religious, social and political organizations, non-governmental organizations (NGOs), unscrupulous government officials, government security, and campus activists (Rahmah & Soetarto, 2015;Anggraini, 2011;Hamidah, 2010;Hartoyo, 2011;Imadudin & Sofianto, 2012;Ilyas, 2018;Imadudin, 2015;Iswari et al, 2018;Kamaruddin, 2012;Lestari & Purwandari, 2015;Muntholib, 2009;Purwandari & Kolopaking, 2012;Rachmawati et al, 2019;Susanto, 2015;Syawaludin, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, agrarian affairs in Indonesia involve the loss of access to land for farmers and conflicts due to disparity in agrarian resource control (Habibie et al, 2021;Lestari, 2014;Suharto & Basar, 2019;Sudiyono et al, 2016). Agricultural lands that have always become agrarian resources have given rise to various problems, such as agrarian technical relations and Jurnal Socius: Journal of Sociology Research and Education socio-agrarian relations that highlight the relationship between agricultural society and agricultural lands (Nugraha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Untuk tahun 2011, konflik agraria yang terjadi adalah 169 kasus, yang melibatkan 69.975 kepala keluarga dan total luas areal konflik mencapai 472 048.44 hektar. Jumlah 169 tersebut, terdiri dari 97 kasus di sektor perkebunan, 36 kasus di sektor kehutanan, 21 kasus di sektor infrastruktur, 8 kasus di sektor pertambangan, dan 1 kasus di wilayah pesisir (Lestari & Purwandari: 2014). Data-data tersebut memperlihatkan bahwa permasalahan sumberdayaterjadi pada berbagai aspek dengan melibatkan berbagai aktor.…”
unclassified